Quevedo Family Oral History - Quevedo, Cameron (My University, 2013)
This project is comprised of oral history interviews from the Quevedo-Bedoya family. The themes explored in these interviews include migration, enculturation, Indigenous identity and cultural perseverance.
Thesis (Master's)--University of Washington, 2013
Keywords: communication; documentary; oral history; Communication; communications